Experimental Study On Powder Coated Surface With Polydur Zinc Based Filler - Lim, Jou Wyn (Universiti Sains Malaysia, 2022)
Powder coating is commonly used in industry to provide a smooth surface finish and protection from the atmosphere. To fix minor defects on metal surface, Polydur Zinc based filler is applied on the surface of the metal to achieve smooth surface before powder coating. However, orange peel is one of the common defects found after curing process and it result in high rejection rate. The aim of this research is to study the parameter influencing the surface after curing process. The effect on surface was investigated using a two-level fractional factorial design with five factors and two variation levels. The tested factors were material, thickness, voltage, curing time and heat profile. The response of surface roughness was used to investigate the orange peel. The effect of each parameter on orange peel was studied using ANOVA and Regression Analysis. Optimal combination of parameters was found for optimum response characteristics. The optimum combination was verified through the experiment, and the fractional factorial design method have successfully improved the quality of powder coating.